GASTRODUODENAL ARTERY ANEURYSM - A CLINICAL CASE REPORT, BRIEF LITERATURE REVIEW - Iv. Tenev; Hr. Atanasov; N. Kovachev; J. Yordanov; D. Petkov (Trakia Journal of Sciences)
The aneurysm of the gastroduodenal artery (AGDA) is a rare, but potentially fatal vascular disease. Chronic pancreatitis is considered to be the leading etiological cause. The most common complication is rupture, which is accompanied by extremely high mortality, due to the rapidly occurring massive blood loss. In such situations, a high index of clinical suspicion, followed by urgent imaging diagnosis and active treatment strategy in case of emergency can prevent a potentially fatal outcome. In the following paper, we present a case of a successfully treated ruptured aneurysm of the gastroduodenal artery(AGDA), that started with minor gastrointestinal bleeding. Endoscopic hemostasis was attempted, followed by an episode of massive recurrent bleeding, requiring emergency operation. A brief literature review, related to the diagnosis and treatment of this rare, but fatal complication of AGDA, is also presented.